2012
DOI: 10.5194/acp-12-7727-2012
|View full text |Cite
|
Sign up to set email alerts
|

Hydration or dehydration: competing effects of upper tropospheric cloud radiation on the TTL water vapor

Abstract: Abstract.A tropical channel version of the Weather Research and Forecasting (WRF) model is used to investigate the radiative impacts of upper tropospheric clouds on water vapor in the tropical tropopause layer (TTL). The WRF simulations of cloud radiative effects and water vapor in the upper troposphere and lower stratosphere show reasonable agreement with observations, including approximate reproduction of the water vapor "tape recorder" signal. By turning on and off the upper tropospheric cloud radiative eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The results indicate that the enhancement of the dehydration process due to the intensification of radiatively driven updraft causes dryer tropopause layers in cases with a larger number of vertical layers. A similar relationship between the radiation and dehydration was reported by Wu et al (2012). They examined the impact of the upper tropospheric cloud radiative effect on the hydration/dehydration in the TTL and found that the enhanced vertical ascent due to upper tropospheric cloud radiative effect contributes the dehydration in the TTL.…”
Section: Journal Of Advances In Modeling Earth Systemssupporting
confidence: 73%
See 1 more Smart Citation
“…The results indicate that the enhancement of the dehydration process due to the intensification of radiatively driven updraft causes dryer tropopause layers in cases with a larger number of vertical layers. A similar relationship between the radiation and dehydration was reported by Wu et al (2012). They examined the impact of the upper tropospheric cloud radiative effect on the hydration/dehydration in the TTL and found that the enhanced vertical ascent due to upper tropospheric cloud radiative effect contributes the dehydration in the TTL.…”
Section: Journal Of Advances In Modeling Earth Systemssupporting
confidence: 73%
“…The radiative heating rate was larger near the tropopause layers in the L78 case than that for L38; the magnitudes of the heating rate in the simulations with L78 were about twice as large as those in the simulations with L38. The strengthening of the radiative heating can lead to the enhancement of the dehydration process through the intensification of radiatively forced updraft, as discussed by Wu et al (2012). This analysis revealed that the enhanced dehydration due to the diabatic updraft by radiative heating leads to the smaller relative humidity near the tropopause of the convective cores and makes the radiation-sedimentation feedback less effective.…”
Section: 1029/2018ms001386mentioning
confidence: 88%
“…following Chen et al (2018) and Wu et al (2012). The vertical dimension is resolved by 29 full sigma levels, with 16 layers located in the lowest 2 km for finer resolution in the planetary boundary layer, and the height of the first layer averaged in BTH is about 30 m.…”
Section: Model Configurationmentioning
confidence: 99%
“…The measurement uncertainties (including biases) are 20% in the UT (p > 100 hPa) and 10% near the tropopause and in the stratosphere (p ≀ 100 hPa) [Read et al, 2007]. As a unique UTLS observational data set, the Aura MLS H 2 O data have been used extensively in atmospheric process analysis studies and model evaluations [e.g., Su et al, 2006;Fu et al, 2006;Liu et al, 2007;Liu and Zipser, 2009;James et al, 2008;Flury et al, 2008Flury et al, , 2013Pittman et al, 2009;Solomon et al, 2010;Takashima et al, 2010;Tian et al, 2011;Wu et al, 2012;Jiang et al, 2012;Dessler et al, 2013;Uma et al, 2014;Takahashi et al, 2015]. Here we use the Aura MLS data as a benchmark to evaluate the performance of the UTLS H 2 O fields produced by the analysis and reanalysis systems.…”
Section: Satellite Observationsmentioning
confidence: 99%